Factors Associated with Quality of Life among People Living with HIV/AIDS in Kupang - Buntoro, Ika Febianti; Arsita, Elli; Handoyo, Nicholas Edwin; Nurina, Rr. Listyawati; Folamauk, Conrad Liab Hendrixson (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2024)
It is known that HIV/AIDS remains a global health problem. Living with HIV/AIDS can have significant impacts on various aspects of life, including mental health, social relationships, and overall well-being. Addressing stigma and discrimination is crucial in improving the quality of life for people living with HIV/AIDS, along with providing access to proper medical care and support services. This study aims to investigate factors that impact the quality of life of people living with HIV/AIDS (PLWHA) in Kupang City, Indonesia from April 2023 to July 2023 in hospitals and NGOs in the city. The design of this study was a cross-sectional study. The study involved 98 respondents, who were PLWHA taking ARV therapy at Prof. Dr. WZ Johannes Public Hospital Kupang and Wirasakti Army Hospital Kupang. The data was collected using the Oslo Social Support Scale (OSSS-3) Questionnaire. This study found that most respondents have moderate social support. The study identified several factors significantly impacting the quality of life for HIV/AIDS patients such as social support (p 0.001), adherence to ARV therapy (p 0.000), depression levels (p 0.007), education level (p 0.002), income level (p 0.012), and the duration of the diagnosis (p 0.044). This study contributes to add valuable information for a comprehensive understanding of the multifaceted challenges faced by individuals living with HIV/AIDS, paving the way for targeted interventions and support strategies.